Redundancy insurance is not unemployment insurance - WU, Zhengxiao (Institutional Knowledge at Singapore Management University, 2020)
In a commentary, SMU Senior Lecturer of Statistics Wu Zhengxiao discussed the difference between redundancy insurance and unemployment insurance. He shared Japan's example, where the cost for unemployment insurance is higher than redundancy insurance, and added that being an unprecedented policy, more care should be taken when implementing it.